Method of Assessing the Impact of Polish Container Terminals in Reducing the External Costs of Transport - Kotowska, Izabela (Promet - Traffic&Transportation, 2013)
The paper attempts to identify the social costs and benefits of marine container terminal operations regarding feeder vessels services. It presents a method of valuation which takes into account the external costs of additional factors: the nature and direction of the shipping lines operated by the terminals and the size of port hinterland. Based on the proposed method, the impact of container terminals to reduce the external costs of transport has been assessed.